2020
DOI: 10.1187/cbe.20-06-0126
|View full text |Cite
|
Sign up to set email alerts
|

A Pandemic Crash Course: Learning to Teach Equitably in Synchronous Online Classes

Abstract: A professional learning community in which faculty explored equitable teaching online is described. This article describes concrete practices other instructors can use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
(63 reference statements)
0
26
1
2
Order By: Relevance
“…While we did not analyze the specific Guiding practices implemented by each instructor, we can infer that the online environment gave them opportunities to incorporate more active learning practices, especially with the addition of the online functions. Our findings contradict previous studies concluding that ERT had a negative impact on student engagement (Perets et al, 2020;Reinholz et al, 2020) and loss of interaction and communication between instructors and their students (Petillion & McNeil, 2020).…”
Section: Instructors Who Guided More In the Online Environment Had Increased Student Working And Talking Behaviorscontrasting
confidence: 99%
See 2 more Smart Citations
“…While we did not analyze the specific Guiding practices implemented by each instructor, we can infer that the online environment gave them opportunities to incorporate more active learning practices, especially with the addition of the online functions. Our findings contradict previous studies concluding that ERT had a negative impact on student engagement (Perets et al, 2020;Reinholz et al, 2020) and loss of interaction and communication between instructors and their students (Petillion & McNeil, 2020).…”
Section: Instructors Who Guided More In the Online Environment Had Increased Student Working And Talking Behaviorscontrasting
confidence: 99%
“…Some instructors may choose to implement a synchronous classroom format (e.g., videoconference call or live online sessions) to encourage student-instructor interactions and group work in the online learning environment (Heiss & Oxley, 2021;Van Heuvelen et al, 2020). However, teaching in a synchronous format does not guarantee student participation; for example, Reinholz et al (2020) found an overall decrease in student participation in biology classrooms as the class transitioned from in-person to synchronous instruction during emergency remote teaching (ERT). In contrast, instructors may choose an asynchronous format (e.g., recorded lectures, discussion boards, and at-home assignments) if they are concerned about their students' abilities to attend live online lectures (Van Heuvelen et al, 2020).…”
Section: Introduction Disruptive Events Led To Innovative Pedagogical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the COI framework has been tested for online learning and K-12 teachers during ERT (Whittle et al, 2020), it has only recently been used for ERT in undergraduate STEM classrooms at a Minority-Serving Institute (MSI). For example, Reinholz et al used the COI framework to study how the nature of student participation changed in moving from face-to-face to synchronous online learning environments at an Hispanic serving institute (HSI) (Reinholz et al, 2020) and Eriksen et al studied how student perceptions of social presence, cognitive presence, and teaching presence online due to COVID-19 were influenced by student demographics (Erickson & Wattiaux, 2021). (Wood et al, 1976) and many researchers and educators have used the concept of scaffolding to describe instructor roles as more knowledgeable peers for guiding student learning and development (Hammond, 2001;Stone, 1998;Wells, 1999).…”
Section: Community Of Inquirymentioning
confidence: 99%
“…The COVID-19 pandemic was upon us. Learners and instructors were isolated, homebound, and forced to communicate online with various make-do strategies-some successful and others not so much (13)(14)(15)(16)(17)(18)(19)(20). Here we describe how several hundred science instructors managed to endure and thrive by using case studies as part of their online instruction survival kit.…”
Section: Introductionmentioning
confidence: 99%